Prevalencia de parásitos en hígado y pulmón de ungulados silvestres de la Reserva Nacional Pucacuro y Comunidad Nueva Esperanza, Loreto-Perú - Echevarria Cauper, Diego Sebastian (2024)
The study was quantitative, observational, cross-sectional, realized with the purpose of knowing the prevalence of parasites in the liver and lung of wild ungulates from the Pucacuro National Reserve and the Nueva Esperanza Community, Loreto-Peru. The samples were collected by hunters for self consumption; however, fluids and viscera were saved for later studies, and the organs were preserved in 10% formalin. These organs were directly observed to find the parasites macroscopically with the help of the stereoscope, they were rinsed with lactophenol and then identified under the microscope using taxonomic keys. Seven tissue parasites belonging to the genera Metastrongylus, Aspidodera, Paraspidodera, Parabronema, Paragonimus, Linguatula and the family Filariidae were identified. In huangana a prevalence of 54.05% was recorded and in sajino 50%, which in both cases corresponds to an average prevalence. The most prevalent parasite was Linguatula with 23.5% and the least prevalent were Aspidodera, Filariidae and Paragonimus with 1.97% respectively. In huangana, the most prevalent tissue parasite was Metastrongylus with 24.32% and in sajino, it was Linguatula with 35.71%. According to the parasitized organ, in huangana a prevalence of 48.64% was recorded in the lung and 8.10% in the liver; while, in sajino, a prevalence of 28.57% was recorded in both organs. The most prevalent genus per organ in peccary liver was Linguatula (28.57%), followed by Metastongylus (24.32%) in Huangana lung and Parabronema (14.29%) in peccary lung. The prevalence of tissue parasites in ungulates from the National Reserve Pucacuro was 61.90% and of those from the Nueva Esperanza Community it was 33.33%. The similar parasite genera in both hosts were Metastrongylus and Linguatula, reaching an average similarity of 44% according to the Sörensen index. In conclusion, the prevalence by parasites, by host and by parasitized organ were different.